The impact of the oil and gas industry on TENORM of the desert sands in Ma’rib, central Yemen - Hongtao Zhao; Mohsen M.M. Ali; Zhigang Li; Abdullah Rawashdeh; Ibrahim Alfasatleh; Omar Alqudah; Waleed Alquraishi; Ahmed Al-Osta (Kuwait Journal of Science)
A measurement of technologically enhanced natural occurring radioactivity materials (TENORM) in sand samples in the petroleum producing communities of Ma'rib Province Yemen was carried out. The HPGe detector was utilized to perform the measurements. The samples collected from 35 sites. All samples were placed in a properly cleaned container and sealed for 28 days so as to attain a state of secular radioactive equilibrium before analysis. The radioactivity concentrations for nuclides 40K, 232Th, 226Ra, and 238U ranged between 430.716 - 654.666, 4.347 - 43.935, 4.824 - 27.936, and 1.083 - 15.437 Bq.Kg-1 respectively, with averages  560.583, 20.676, 14.556  and 9.072 respectively. The results not show any radiation risks.